From 153-year-old records to contemporary discoveries: land snail (Mollusca, Gastropoda) diversity in Penang Hill, Malaysia - Soo-Mun Goh; Dulipat Jasrul; Mei-Yi Lee; Jaap J. Vermeulen; Thor-Seng Liew (ZooKeys)
This study highlights the diversity of land snails in Penang Hill, a non-limestone hill in Peninsular Malaysia. A systematic survey of land snails in Penang Hill was conducted, inventoried, and compared with those specimens collected by Stoliczka (1872, 1873) in 1869. Based on the 33 sampling plots established in this study, the differences in species composition along the elevation gradient (75 m to 770 m a.s.l.) and between three different habitats on Penang Hill were examined: disturbed forests with anthropogenic activities, undisturbed forests, and orchards with various crops. A total of 54 species were recorded from the sampling plots and random observations, of which only 20 overlapped with Stoliczka’s list; 34 were new records for Penang Hill, and 12 previously recorded species were not found in this study. Most of the new records were micro-snails smaller than 5 mm. Species richness was highest in disturbed forests and showed no correlation with elevation. There was no clear grouping of plots by species composition across habitat types, except for those in orchards. Indicator species analysis revealed strong associations between a few land snail species and disturbed forests and orchards. The number of species in Penang Hill increased from 32 to 66, with species richness comparable to the high numbers usually found in limestone habitats and higher mountains in Malaysia.